http://archaeologie.pro/en/archive/8/141 - Orfinskaya Olga V.; Nikitina Tatyana B. (Поволжская археология, 2014)
The article summarizes primary results of technological analysis of textile fragments (45 items) from the Mari 9th-10th-century burials located at the Rusenikha and Nizhnyaja Strelka burial ground sites in the Vetluga-Vyatka interfluve area. Six textile groups have been singled out: 1) woolen fabric of plain weave; 2) woolen fabrics of twill weave; 3) plain weave cloths from plant fibers; 4) silk fabrics; 5) cords and cord tassels from woolen yarn; 6) fragments of felt. They are remains of garments, mats and fabrics used for wrapping funerary gifts. An attempt to reconstruct the cut of individual parts of the garments has been made by the authors.